THE DEVELOPMENT OF HALAL TOURISM DESTINATIONS MODEL BASED ON ART CULTURE PERFORMERS OF SAPI SONOK MADURA IN PAMEKASAN REGENCY - Rio Kurniawan; Lian Agustina Setiyaningsih (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
This research aims to create a model for the development of halal tourism destinations based on the perspectives of the actors of the Sapi Sonok culture in Pamekasan, Madura. The challenge for tourism development after the pandemic is forming a concept that adheres to local wisdom. Cultural tradition can inspire the development of tourism destinations without exploiting the values of the local residents. The phenomenological approach was employed through an interpretive paradigm, and four informants were recruited through purposive sampling. Data were collected through in-depth interviews, documentation, and observation. Meanwhile, analysis techniques use bracket; intuitive; analysis; and description. The research reveals, first, the artistic philosophy of the actors forms social cohesion even though there is competition within it. The actors’ philosophy includes beauty contests and the beauty of animals; tancek-guyup, harmony, and gratitude as well as social cohesion. Second, harmonious forms of cultural identity are adapted to local values. Halal tourism communication methods include observation, accessibility, amenities, and promotion of business actors. Finally, the right model is the one to develop halal tourism destinations based on the cultural actors of the Madurese Sapi Sonok culture which refers to the strength of the internal community and external groups.